Employees’ Turnover Behaviour of Secretary Firms in Malaysia - Chiam, Sun Hua (2019)
Over the years, company secretaries in Malaysia play increasing role and responsibilities due to changing corporate environment that focuses more on money laundering issues and good corporate governance. As a legally named officer in a company, the company secretary is relied upon to play compliance and advisory role. Digitalization also means that company secretaries, who are assigned as e-lodger of all statutory submissions to the Companies Commission of Malaysia, will assume full and sole responsibility to verify all information submitted to the Registrar. While increasing employees turnover rate has become a concern to all corporate entities, professional service based industry such as company secretaries rely heavily on the consistency of services provided. This study attempts to understand organizational behaviour of employees in secretary firms and to identify the most relevant factors contributing to turnover behaviour. This paper uses quantitative methods on samples collected from company secretary firms in Kuala Lumpur and Selangor, and models the causal relationship between organizational commitment, perceived organizational support and job satisfaction towards turnover intention. In conclusion, this study finds that job satisfaction and perceived organizational support are two important factors to turnover intention, while organizational commitment is not an important predictor. Furthermore, study shows that improving an employee’s commitment level to the professional industry, such as pursuing membership and qualification with professional company secretary bodies, can reduce turnover behavior significantly.